2021
DOI: 10.3899/jrheum.210480
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in Pregnant Women With Rheumatic Disease: Data From the COVID-19 Global Rheumatology Alliance

Abstract: Objective To describe coronavirus disease-2019 (COVID-19) and pregnancy outcomes in patients with rheumatic disease who were pregnant at the time of infection. Methods Since March 2020 the COVID-19 Global Rheumatology Alliance (GRA) has collected cases of patients with rheumatic disease with COVID-19. We report details of pregnant women at the time of COVID-19 infection, including obstetric details separately ascertained from providers. Results We report on 39 patients, including 22 with obstetric detail avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 13 publications
2
9
0
2
Order By: Relevance
“…Fever and cough were the predominant symptoms in our pregnant patients, and only a minority needed hospitalization. A similar finding was observed in data from the Global COVID-19 Registry, where only 5% of pregnant women with autoimmune rheumatic diseases required hospitalization with supplemental oxygen, and all eventually recovered [ 6 ].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Fever and cough were the predominant symptoms in our pregnant patients, and only a minority needed hospitalization. A similar finding was observed in data from the Global COVID-19 Registry, where only 5% of pregnant women with autoimmune rheumatic diseases required hospitalization with supplemental oxygen, and all eventually recovered [ 6 ].…”
Section: Discussionsupporting
confidence: 81%
“…This information may be subject to recall bias and needs to be explored in further studies. The rates of caesarean section and prematurity were similar to the data reported by the COVID-19 Global Registry Alliance (GRA) [ 6 ].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Rituximab is a B cell-depleting therapy (BCDT), and BCDTs are also associated with poor outcomes for COVID-19 in people with conditions other than rheumatic diseases 50 . In the third study, researchers reported generally favourable pregnancy outcomes in 39 women with rheumatic disease who had COVID-19 whilst pregnant 51 . The fourth study contained an analy sis of pooled data from the C19-GRA registry and from international registries for people with COVID-19 and inflammatory bowel disease or skin psoriasis, to examine outcomes for people receiving treatment with TNF inhibitors 52 .…”
Section: Key Pointsmentioning
confidence: 94%
“…Несмотря на наличие большого числа публикаций о взаимовлиянии COVID-19 и ИВРЗ, COVID-19 и беременности, данных о течении COVID-19 у беременных с ИВРЗ крайне мало. Наиболее интересными представляются материалы Глобального ревматологического альянса COVID-19 (The COVID-19 Global Rheumatology Alliance), созданного в марте 2020 г. для сбора и анализа информации о COVID-19 и ИВРЗ [12]. С 30 июня 2020 г. по 14 января 2021 г. в регистр было включено 39 беременных с ревматоидным артритом (9), системной красной волчанкой (9), антифосфолипидным синдромом (6), АС (3) и по одной беременной с другими ИВРЗ.…”
unclassified